(untitled) (Research, Society and Development, 2021)
Introduction: This article aims to show the importance of Resolution 216/04 in food and nutrition units with the use of the checklist to assess the hygienic and sanitary standards in these establishments. General Objective: elucidate the importance of resolution nº216 in the Food and Nutrition Units to reduce DTAS in Brazil. Methodology: For the organization of collected data, the use of deductive methodology was used. Results and Discussion: This RDC was created by ANVISA in order to reduce the rates of foodborne illnesses (DTAS) in Brazil. STDs are diseases transmitted by food contaminated by microorganisms such as bacteria, viruses, among others. need to create a manual of good practices in food handling to standardize a kind of script to be followed in these establishments, aiming at the health of customers and handlers. We will also have a brief description of the manual of good food manufacturing practices, which aims to establish standards at the manufacturing sites of any type of product in the food sector, and it will also be mentioned on how to reduce DTAS and also how to identify these diseases according to symptoms presented by people who made the ingestion of these foods contaminated by microorganisms. Conclusion: it was concluded that RCD 216/04 is an important law for the control and prevention of STDs in food and nutrition units (UAN). Its main purpose is the implementation of hygienic sanitary standards to be followed in the UAN so that there is no food contamination.